Modified nutrient management protocol for optimum biomass production, nutritional quality, and flavor-related phytochemical properties of hydroponic-grown kale (Brassica oleracea) - Yang, Teng; Samarakoon, Uttara; Altland, James (Frontiers in Plant Science, 2025)
IntroductionNutrient supply in hydroponic leafy green production is often not aligned with crop-specific requirements. Kale (Brassica oleracea ‘Red Russian’) has been shown to exhibit higher nitrogen (N) demand than other leafy greens. Conventional nutrient management relies on a two-part water-soluble fertilizer system—Part A with macronutrients and micronutrients and Part B with calcium nitrate (Ca(NO3)2)—to maintain electrical conductivity (EC), but this approach may not optimize N supplementation or crop quality.MethodsWe evaluated a modified protocol in which only Ca(NO3)2 was supplied during the final production week, replacing the standard two-part adjustment. Plant biomass, nutrient composition, phytochemicals, and physiological traits of hydroponically grown kale were assessed.ResultsThe Ca(NO3)2-only treatment significantly increased shoot biomass, shoot-to-root ratio, and uptake of N, calcium, and magnesium by 28.5%, 22.1%, 46.0%, 27.5%, and 14.4%, respectively, compared with conventional management, suggesting N and calcium were key limiting factors for shoot growth. Nitrate accumulation in shoots also increased but remained within safe consumption limits. Phytochemical analysis revealed reductions in anthocyanins and vitamin C, alongside a slight increase in glucosinolates. No significant changes were observed in photosynthetic traits, root growth, or water and acid use.DiscussionTargeted N supplementation with Ca(NO3)2 enhanced growth and nutrient uptake in kale but introduced tradeoffs in phytochemical composition. These results underscore the potential of crop-specific nutrient strategies to improve both yield and nutritional quality of hydroponic leafy greens in controlled environment systems.